Serological response to rabies virus induced by commercial vaccines in cattle - Martins,Mathias (2017)
ABSTRACT: The antibody response to rabies virus (RABV) induced by commercial vaccines in heifers was investigated. For this, 84 heifers were vaccinated twice (30 days interval) with each of four vaccines (G1 = 14 animals; G2 = 24; G3 = 22 and G4 = 24) and received a booster vaccination 360 days later. Serum samples collected at different intervals after vaccination and 30 days after booster were submitted to a virus neutralizing (VN) assay for RABV antibodies. Thirty days after the second vaccine dose, 92% of the immunized animals presented VN titers ≥0.5UI/mL (geometric medium titers [GMT] 1.7 to 3.8UI/mL). At the day of the booster (360 days post-vaccination); however, the percentage of animals harboring antibody titers ≥0.5UI/mL had dropped to 31% (0-80% of the animals, depending on the vaccine), resulting in lower GMT (0.1 to 0.6UI/mL). Booster vaccination at day 360 resulted in a detectable anamnestic response in all groups, resulting in 83% of animals (65 to 100%) harboring VN titers ≥0.5UI/mL thirty days later (GMT 0.6 to 4.3UI/mL). These results indicated that these vaccines were able to induce an adequate anti-RABV response in all animals after prime vaccination (and after booster as well). However, the titers decreased, reaching titers <0.5UI/mL in approximately 70% of animals within the interval before the recommended booster. Thus, booster vaccination for rabies in cattle using the current vaccines should be performed before the recommended one-year interval, as to maintain neutralizing antibodies levels in most vaccinated animals.